2022
DOI: 10.3390/jcm11236972
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Multiple Myositis-Specific Antibodies in Patients with Idiopathic Inflammatory Myopathies

Abstract: The mutual exclusivity of myositis-specific antibodies (MSAs) has been reported before, but the coexistence of 2 or more MSAs was still found in a few case reports. This study aims to confirm the existence and prevalence of double MSAs in patients with idiopathic inflammatory myopathy (IIM) and to clarify the clinical features of these patients. One hundred fifty-one patients with IIM diagnosed from 1 July 2018 to 31 July 2022, at National Cheng Kung University Hospital, Taiwan, were enrolled and divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Although their true clinical value has yet to be defined, as they are common to other autoimmune disorders, antibodies to valosin-containing protein (anti-VCP) were detected in 26.0% of patients with sporadic IBM with a significant specificity (87.2%) but low sensitivity (26.0%) (83). Despite the fact that, in most cases, the coexistence of two or more MSAs represents a false positive, double positivity for MSAs is rare but may occur in IIMs, although the clinical phenotype is usually characteristic of only one of them and the double positivity does not seem to have an impact on the severity and prognosis of the disease (84). sparing agents, or both.…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Although their true clinical value has yet to be defined, as they are common to other autoimmune disorders, antibodies to valosin-containing protein (anti-VCP) were detected in 26.0% of patients with sporadic IBM with a significant specificity (87.2%) but low sensitivity (26.0%) (83). Despite the fact that, in most cases, the coexistence of two or more MSAs represents a false positive, double positivity for MSAs is rare but may occur in IIMs, although the clinical phenotype is usually characteristic of only one of them and the double positivity does not seem to have an impact on the severity and prognosis of the disease (84). sparing agents, or both.…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Previous studies observed the coexistence of multiple MSAs in 3%–15% of patients with IIM, with the proportion varying with the test methods. 7 8 It is particularly interesting that the anti-Ro52 antibody has also been the most commonly detected myositis autoantibody in Korean patients with anti-HMGCR myopathy. 3 Further studies with larger study populations that apply multiple antibody detection methods are necessary to determine the clinical implications of the anti-Ro52 antibody in patients with seropositivity for IMNM.…”
mentioning
confidence: 99%